2018
DOI: 10.1111/jfd.12895
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biology of Macrobrachium rosenbergii nodavirus infection in giant freshwater prawn

Abstract: Macrobrachium rosenbergii nodavirus (MrNV) has been threatening the giant freshwater prawn aquaculture since 1997, causing white tail disease in the prawn species that leads to 100% lethality of the infected postlarvae. Comprehension of the viral infectivity and pathogenesis at molecular biology level has recently resolved the viral capsid protein and evidenced the significant difference in the viral structural protein compared to other nodaviruses that infect fish and insect. Cumulative researches have remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 109 publications
1
8
0
Order By: Relevance
“…This observation would have explained the inability to cluster MrNV and PvNV in neither alpha‐ nor betanodavirus due to the distinct amino acid sequence encoded by the significant different nucleotide preference and composition of its capsid. Current findings are in agreement to previous reports on the diversity in capsid topologies among the members of the Nodaviridae (Chen et al, ; Low, Md Yusoff, Kuppusamy, & Ahmad Nadzri, ; Odegard, Banerjee, & Johnson, ), where sequence similarity of both MrNV and PvNV is not more than 20% with that alpha‐ and betanodavirus, whilst the capsid protein sequence similarity is more than 80% between MrNV and PvNV (Chong, Ganesan, Yong, Tan, & Ho, ; NaveenKumar et al, ). This may lead to an assumption of nodavirus capsid evolution in a non‐linear form within the family group (Warrilow et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…This observation would have explained the inability to cluster MrNV and PvNV in neither alpha‐ nor betanodavirus due to the distinct amino acid sequence encoded by the significant different nucleotide preference and composition of its capsid. Current findings are in agreement to previous reports on the diversity in capsid topologies among the members of the Nodaviridae (Chen et al, ; Low, Md Yusoff, Kuppusamy, & Ahmad Nadzri, ; Odegard, Banerjee, & Johnson, ), where sequence similarity of both MrNV and PvNV is not more than 20% with that alpha‐ and betanodavirus, whilst the capsid protein sequence similarity is more than 80% between MrNV and PvNV (Chong, Ganesan, Yong, Tan, & Ho, ; NaveenKumar et al, ). This may lead to an assumption of nodavirus capsid evolution in a non‐linear form within the family group (Warrilow et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…The role of individual virus (MrNV and XSV) in the pathogenesis of WTD is not clearly understood. Even though there are some evidence to show MrNV plays a key role in the pathogenesis of WTD [10] the role of XSV cannot be neglected [11,16]. Studies from Zhang et al [48] have shown XSV to be a satellite virus and several studies have shown that satellite virus acts as pathogenicity factor and also interfere and suppress RNAi mechanisms [27].…”
Section: Specificity and Sensitivity Of Polyclonal Antibodies In Detection Of Mrnv And Xsv Antigensmentioning
confidence: 99%
“…Epidemics generated by viruses and bacteria have seriously impacted commercial prawn farming, resulting in severe economic losses. Viruses, such as white spot syndrome virus, infectious myonecrosis virus and M. rosenbergii nodavirus, have been commonly found to cause diseases in shrimp farming (Low et al, 2018; Prasad et al, 2017; Sánchez‐Paz, 2010), while the bacterial infection affecting shrimp aquaculture is caused by pathogenic Enterococcus sp., Vibrio parahaemolyticus and Aeromonas hydrophila (Chang et al, 2020; Cheng & Chen, 2002; Lai et al, 2015). The farmers are compelled to apply the antibiotic during the culture to reduce the infection of pathogens, promote the immune system and growth rate.…”
Section: Introductionmentioning
confidence: 99%